A Note on the Perturbation Approach to Nonlinear Static Analysis of Elastic Plane Trusses - Saran, M.; Kleiber, M. (Engineering Transactions, 1984)
A perturbation proceduro for the incremental finite element analysis of large deformation problems is presented. The proposed approach takes into account the nonlinearity of kinematics at the incremental step. Explicit forms of the finite element "higher-order" matrices for truss element and numerical examples are given. Comparison of the results obtained by the perturbation approach, tangential stiffness method and closed-form solution are carried out. The appropriate computational cost analyses are presented implying conditions for the economical use of the method.